The Challenging Subway Project in Bangkok - New Hope of Thais in Solving Traffic Problem [Keynote] - Suchatvee Suwansawat (My University, 2003)
This paper describes the overall delivery of the Chaloem Ratchamongkhon Line, the first subway project in Bangkok as a challenging tunneling project in an urban environment.Eight pressure balance shields were employed under two major civil works contracts (North and South sections) to drive approximately 20 kilometers of twin-tunnel underneath congested area.As a international well known project, multinational workforces exca vated tunnels for the large subway system intended to carry a half million people daily over several lines through the central city in order to minimize traffic jam.Tunnel problem includes many existing structures along the tunnel route as well as flooding, ground subsidence, and fire problems.
Keywords: Underground infrastructure and sustainability